2015
DOI: 10.1051/0004-6361/201526386
|View full text |Cite
|
Sign up to set email alerts
|

The center-to-limb variation across the Fraunhofer lines of HD 189733

Abstract: The center-to-limb variation (CLV) describes the brightness of the stellar disk as a function of the limb angle. Across strong absorption lines, the CLV can vary quite significantly. We obtained a densely sampled time series of high-resolution transit spectra of the active planet host star HD 189733 with UVES. Using the passing planetary disk of the hot Jupiter HD 189733 b as a probe, we study the CLV in the wings of the Ca  H and K and Na  D 1 and D 2 Fraunhofer lines, which are not strongly affected by ac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
115
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 97 publications
(126 citation statements)
references
References 70 publications
11
115
0
Order By: Relevance
“…But A sp is more important for determining The strongest absorption signal, or in this case contrast signal, is when the planet is near the edge of the stellar disk but still almost completely covers the limb. This is very similar behavior to the Na I D calculations presented by Czesla et al (2015).…”
Section: A Note On Parameter Importancesupporting
confidence: 89%
See 1 more Smart Citation
“…But A sp is more important for determining The strongest absorption signal, or in this case contrast signal, is when the planet is near the edge of the stellar disk but still almost completely covers the limb. This is very similar behavior to the Na I D calculations presented by Czesla et al (2015).…”
Section: A Note On Parameter Importancesupporting
confidence: 89%
“…They demonstrated that the Na I lines show limb-brightening in the wings of the line compared with the line core or neighboring continuum. This is important since a transiting planet with no atmosphere can produce a transmission signal, even if there are no active regions present on the stellar surface, due to the fact that the ratio of the line core to the continuum changes as a function of the transit (see Figures 1-5 of Czesla et al 2015). This effect was recently included in Na I transit modeling by Khalafinejad et al (2016).…”
Section: Contrast and Limb-darkening/brighteningmentioning
confidence: 99%
“…1 and Czesla et al 2015). Czesla et al (2015) compare the integrated flux from the individual chips with model spectra (Castelli & Kurucz 2004;Kurucz 1970) and a blackbody spectrum and find that they generally agree well (see their Table 4); they further attribute the remaining variations in the observed flux of about 20% (also shown in Fig. 1) to slit losses and the residual influence of airmass and atmospheric conditions.…”
Section: Observations and Data Reductionmentioning
confidence: 73%
“…This dip can probably be attributed to the center-to-limb variation, which is described in more detail in Czesla et al (2015).…”
Section: Temporal Evolution Of the Chromospheric Activity Indexmentioning
confidence: 89%
See 1 more Smart Citation